Old concepts, new publics: CSR and millennials - Eiró-Gomes, Mafalda (2017)
Since the beginning of the new millennium, concepts as those of hypermodernity or post-truth seem to have invaded all our spheres of activity. Along with the effective changes and challenges brought up by technology, there is indeed a new generation with new interests, habits and desires (Strauss & Howe, 2000) that organizations should comprehend in order to successfully address and relate with them as stakeholders.